Translating Ballet to Change Perceptions and Engage Community College Students. Issue 4 (13th December 2022) - McClam, Nicole Y.
Abstract: My community college students have diverse backgrounds but tend to share a narrow perception of ballet. To shift their thinking toward ballet as a learning tool instead of a measurement of what they lack, I created assignments meant to unpack their history with ballet, identify what they hope to learn in ballet class, and begin to "own" the technique. A self-reflection of my educational values inspired me to disrupt the routine teaching in ballet focused on technical learning and replication, which presented ballet as dictates to follow rather than movements to explore, and instead to invite the students to use what they know to demystify ballet and become more thoughtful, perceptive dancers.